2013
DOI: 10.1093/cvr/cvt133
|View full text |Cite
|
Sign up to set email alerts
|

Junctophilin-2 is necessary for T-tubule maturation during mouse heart development

Abstract: Our findings suggest that JPH2 is necessary for TT maturation during postnatal cardiac development in mice. In particular, JPH2 may be critical in anchoring the invaginating sarcolemma to the sarcoplasmic reticulum, thereby enabling the maturation of the TT network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 30 publications
7
121
2
Order By: Relevance
“…JPH2 overexpression had comparatively little impact on the t-system morphology similar to findings in Guo et al (2014). Detailed analysis showed an increase in longitudinal t-system connections (by ∼10%) which might result from the role of JPH2 in the development of the t-system (Chen et al, 2013;Reynolds et al, 2013), but importantly this does not lead to any detectable impact on Ca 2+ handling in intact myocytes. Taken together, the moderate effect on t-system architecture in conjunction with essentially normal Ca 2+ handling in JPH2-OE murine myocytes in a mouse model independently developed from that shown in Guo et al (2014) shows that these are robust observations that do not depend on details of the overexpression system, which is important when considering its therapeutic potential.…”
Section: Discussionmentioning
confidence: 69%
“…JPH2 overexpression had comparatively little impact on the t-system morphology similar to findings in Guo et al (2014). Detailed analysis showed an increase in longitudinal t-system connections (by ∼10%) which might result from the role of JPH2 in the development of the t-system (Chen et al, 2013;Reynolds et al, 2013), but importantly this does not lead to any detectable impact on Ca 2+ handling in intact myocytes. Taken together, the moderate effect on t-system architecture in conjunction with essentially normal Ca 2+ handling in JPH2-OE murine myocytes in a mouse model independently developed from that shown in Guo et al (2014) shows that these are robust observations that do not depend on details of the overexpression system, which is important when considering its therapeutic potential.…”
Section: Discussionmentioning
confidence: 69%
“…Initially, JPH2 was reported to function as a tether that connects the PM to the SR within the cardiac dyad (19,23). Recent studies, however, have also demonstrated that JPH2 acts as a critical regulator of cardiomyocyte development by promoting the maturation of transverse tubules (21). In addition, JPH2 was shown to modulate intracellular Ca 2ϩ handling through regulation of RyR2 (6,25).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of JPH2 was shown to increase variability in the distance between the PM and SR, whereas the mean distance remained unaltered. Moreover, JPH2 has also been shown to directly bind to and inhibit RyR2 function, suggesting that JPH2 might have nonstructural roles in cardiomyocytes (11,21). Cardiac-specific conditional knockdown of JPH2 resulted in increased RyR2 sparking and channel opening with resultant decrease in CICR and ECC gain (27).…”
mentioning
confidence: 99%
“…Caveonlin-3 organized caveolae distributes along t-tubules and caveolae distribution is altered in Bin1-deleted mouse cardiomyocytes (Laury-Kleintop et al, 2015), indicating crosstalk between cBIN1-microdomains and caveolae microdomains within t-tubules. JPH2 is a t-tubule/jSR junctional protein and is involved in the maintenance of junctional membrane structure, which when knocked down increases the distance between t-tubule and jSR membrane and disrupts jSR membrane complexes (van Oort et al, 2011;Wu et al, 2012;Reynolds et al, 2013). A role of JPH2 in HF progression has been reported (see review in (Takeshima et al, 2015)).…”
Section: The Role Of Bin1 In T-tubule Microdomain Organization and Fumentioning
confidence: 99%